2019
DOI: 10.4314/wiojms.v18i1.7
|View full text |Cite
|
Sign up to set email alerts
|

The status of Mtwapa Creek mangroves as perceived by the local communities

Abstract: Aims and scope: The Western Indian Ocean Journal of Marine Science provides an avenue for the wide dissemination of high quality research generated in the Western Indian Ocean (WIO) region, in particular on the sustainable use of coastal and marine resources. This is central to the goal of supporting and promoting sustainable coastal development in the region, as well as contributing to the global base of marine science. The journal publishes original research articles dealing with all aspects of marine scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
(39 reference statements)
0
9
0
1
Order By: Relevance
“…The majority of family heads were the sole bread winner and also obtained their monthly income through formal employment in different sectors. Therefore, in this study poverty was insignificant as compared to a similar study in Kenya where local communities were found to be highly dependent on the mangroves as a means to diversify their source of income due to lack of other opportunities and low levels of education (Okello, 2019).…”
Section: Socio-demographic Profile Of Local Residentsmentioning
confidence: 54%
See 3 more Smart Citations
“…The majority of family heads were the sole bread winner and also obtained their monthly income through formal employment in different sectors. Therefore, in this study poverty was insignificant as compared to a similar study in Kenya where local communities were found to be highly dependent on the mangroves as a means to diversify their source of income due to lack of other opportunities and low levels of education (Okello, 2019).…”
Section: Socio-demographic Profile Of Local Residentsmentioning
confidence: 54%
“…This indicated that with more awareness, the high frequency of respondents who opined "I have no idea" and "It is an eyesore obstructing the beautiful scenery of the sea" would decrease. Consequently, the findings of this study are interesting and unique in the sense that studies from other counties (Okello, 2019;Naylor et al, 1998) reported that local communities who lived adjacent to mangrove ecosystems had an adequate level of knowledge on their goods and services. Thus, it is apparent that public understanding and awareness with respect to the mangrove biological and economical values can be improved if the local community is made aware of the full potential benefits that could be derived from the mangrove forest (Rahman and Asmawi, 2016).…”
Section: Perception Of Local Residents Towards the Goods And Services...mentioning
confidence: 74%
See 2 more Smart Citations
“…Due to this fact, majority of the dwellers are reluctant in using lagoon water for their daily use. However, such kind of livelihood transformations are not uncommon in Sri Lanka as well as the other parts of the world (Okello et al 2019;Madarasinghe et al 2020aMadarasinghe et al , 2020b.…”
Section: Discussionmentioning
confidence: 99%